Rancang Bangun Aplikasi Sistem Pendukung Keputusan Untuk Pemilihan Perumahan Menggunakan Metode SAW (Simple Additive Weighting) - Harun Sujadi; Ady Kurniawan (PROCEEDING STIMA)
In taking the decision to solve a problem is not easy, in this case the decision in the selection of housing. To resolve the problem required a decision support system application. Where the application is a system that helps decision-makers to equip them with information from data that has been processed by the relevant and necessary to make a decision about a problem more quickly and accurately. One problem resolution to assist in decision-making is the simple additive weighting method (SAW). SAW method is often also known as a weighted sum. The basic concept is to find the SAW method of rating the performance of a weighted sum of each alternative on all attributes. SAW method requires a decision matrix normalization process (X) to a scale which can be compared with all the rating alternatives. In the application development process using the method Diman RUP RUP provides a disciplined approach to assigning tasks and responsibilities within the development organization. In RUP, there are four phases: Inception, Elaboration, Construction and Transition.Kata kunci: housing, simple additive weighting (SAW), RUP